2020
DOI: 10.1155/2020/9369758
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Profile of Adults with Malaria Parasitaemia Visiting the Volta Regional Hospital, Ghana

Abstract: Background. Malaria is known to cause severe health consequences due to its marked effects and alteration on the haematological parameters of infected individuals. This study evaluated the haematological profile of adult individuals infected with the malaria parasite. Methods. A retrospective study was conducted using archived data of malaria positive cases from January 2017 to March 15, 2019. Data retrieved included subjects’ demographics, malaria parasite count, malaria parasite species, and full blood count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 13 publications
7
11
2
Order By: Relevance
“…The current study revealed that the mean Hb concentration and RBC counts were signi cantly lower in patients than in controls. This is in agreement with previous studies (Erhabor et al, 2014;Sakzabre et al, 2020). In endemic areas, anemic individuals are more likely to be malaria positive than the non-anemic counterparts (Nlinwe and Nange, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study revealed that the mean Hb concentration and RBC counts were signi cantly lower in patients than in controls. This is in agreement with previous studies (Erhabor et al, 2014;Sakzabre et al, 2020). In endemic areas, anemic individuals are more likely to be malaria positive than the non-anemic counterparts (Nlinwe and Nange, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Total WBC counts are generally low to normal during malaria, this is widely thought to re ect their localization away from the peripheral circulation (McKenzie et al, 2005). Contrary to the present study ndings, leukocytosis, neutropenia, monocytosis were observed in some patients (Maina et al, 2010;Sakzabre et al, 2020). Lymphocytosis was associated with falciparum malaria mortality among children (Ladhani et al, 2002).…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Pancytopenia, like in the case we presented, has also been observed frequently. Sakzabre et al, in a retrospective analysis in Ghana, observed lymphopenia (56.78%), anaemia (55.51%), thrombocytopenia (47.46%), eosinopenia (45.76%), neutropenia (29.24%), monocytosis (21.19%), and leucocytosis (17.37) in infected patients (23). However, they had a signi cant number of cases due to P. malariae (12.7%), and this may have altered the clinical picture.…”
Section: Discussionmentioning
confidence: 96%
“…Malaria parasite is a blood parasite that causes different hematological abnormalities such as anemia, thrombocytopenia, lymphopenia, monocytosis, eosinopenia, and rarely disseminated intravascular coagulation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%